Relationships Between Soil Carbon and Soil Texture in the Northern Great Plains. Issue 8 (August 2016) - Augustin, Christopher; Cihacek, Larry J.
Abstract : Abstract: The amount of carbon (C) sequestered in soil is related to soil texture, soil management, vegetation, and climatic variation. However, in the Northern Great Plains, little information is available to quantify the effects of soil texture on the C sequestration potential of soils. This work was conducted to develop relationships for C sequestration potential based on soil texture under a variety of agricultural practices. Soil samples were collected from central and southeast North Dakota from sites with differing soil management and cropping systems; this includes native prairie, differing Conservation Reserve Program year classes, no-till, and conventional tillage practices. Particle size analysis was determined on the 0- to 15-cm soil depth using a hydrometer method. Sand fractions were determined by sieving. Carbon analysis was done by a high temperature combustion method. For all sampled soils, total silt (%) was found to be positively correlated ( P ⩽ 0.01) to organic C content (percent organic C) and organic C mass (kg m −2 depth −1 ). Sand was found to be negatively correlated ( P ⩽ 0.10) with % organic C and organic C mass. Soil clay content was correlated with organic C mass ( P ⩽ 0.05) but not percent organic C. Bulk density was found to be negatively correlated with percent organic C ( P ⩽ 0.10). The strong correlation between silt content and soil organic C reflects the greater water holding capacity and plant available water of silt-dominated soils, which, in turn, affect plant productivity and influences C sequestration in soil.